Biology and Seasonality of Lace bug Cochlochila bullita (Stal) (Heteroptera: Tingidae) on Tulsi Ocimum sanctum L. - Das, Umesh; Pal, Suprakash; N, Ponnusamy (International Journal of Bio-resource and Stress Management, 2020)
An experiment was conducted to study the biology and seasonal incidence of lace bug, Cochlochila bullita (Stal) infesting tulsi (Ocimum sanctum L.) at Uttar Banga Krishi Viswavidyalaya, Pundibari, West Bengal, India. The incubation period varied from 4-6.5 days (average 5.45±0.762 days) and 4-7.5 days (average 5.60±1.220 days) during June, 2018 and August, 2018 respectively. Similarly, the nymphal period of 1st instar lasted from 2-4.5 days (average 2.95±0.832 days) and 2-4 days (average 3.3±0.714 days), 2nd instar lasted from 2-4 days (average 3.10±0.738 days) and 2-4 days (average 3.15±0.668 days), 3rd instar lasted from 2-3 days (average 2.45±0.497 days) and 2-3.5 days (average 2.65±0.579 days), 4th instar lasted from 1.5-2.5 days (average1.90±0.316 days) and 1-3 days (average1.80±0.674 days), 5th instar lasted from 1-2.5 days (average 1.45±.599 days) and 1-2 days (average 1.60±.459 days) during two study periods, respectively. The total nymphal period varied from 8.5-15 days (average 11.85±1.749 days) and 9.5-15.5 days (average 12.5±2.160 days). The total life span of lace bug ranged from 41-52 days (average 46.85±3.448 days) and 43-55.5 days (average 48.45±3.840 days) during two consecutive studies. The lace bug population commenced in the field during second fortnight of June and attained the peak (35.00/10 cm twig) in the first fortnight of December. More lace bug was recorded during the winter season and population declined in the month of February. The lace bug population registered significant negative correlation with abiotic temperature. However multiple regression analysis of lace bug population with abiotic factors revealed limited influence of weather parameters on the population of the pest.